2013
DOI: 10.1186/1471-2148-13-246
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to infectious disease in East African Shorthorn Zebu: a genome-wide analysis of the effect of heterozygosity and exotic introgression

Abstract: BackgroundPositive multi-locus heterozygosity-fitness correlations have been observed in a number of natural populations. They have been explained by the correlation between heterozygosity and inbreeding, and the negative effect of inbreeding on fitness (inbreeding depression). Exotic introgression in a locally adapted population has also been found to reduce fitness (outbreeding depression) through the breaking-up of co-adapted genes, or the introduction of non-locally adapted gene variants.In this study we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…However, in developing countries, pedigree and performance recording remain a bottleneck for the implementation of selection schemes . More generally, genomics provides effective tools to assess and monitor the level of introgression within local population (Leroy et al, 2012;Murray et al, 2013). Genome-wide analysis of crossbred and improved livestock under tropical conditions may also reveal the genomic regions submitted to recent selection and therefore linked to adaptation, as investigated by Kim and Rothschild (2014) in Kenyan dairy cattle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in developing countries, pedigree and performance recording remain a bottleneck for the implementation of selection schemes . More generally, genomics provides effective tools to assess and monitor the level of introgression within local population (Leroy et al, 2012;Murray et al, 2013). Genome-wide analysis of crossbred and improved livestock under tropical conditions may also reveal the genomic regions submitted to recent selection and therefore linked to adaptation, as investigated by Kim and Rothschild (2014) in Kenyan dairy cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular approaches may also provide valuable information on the level of crossbreeding with local populations. In Kenya, Murray et al (2013) performed genomic analysis on a sample of 500 East African Shorthorn Zebu and reported average introgression levels around 2%, with 20% of calves showing levels of introgression consistent with crossing with European breeds â©œ5 generations ago. A study of the same data revealed a greater rate of European introgression in closer proximity to animal markets (Mbole-Kariuki et al, 2014).…”
Section: Evidence Of Crossbreeding In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that, following repeated annual exposure to migrating wildebeest, the African breed is more resistant to AlHV-1. This view is supported by recent genetic studies on the closely-related East African Shorthorn Zebu, which provide evidence of selection for traits related to survival in the African environment, including factors such as resistance to endemic pathogens (Bahbahani et al, 2015, Murray et al, 2013). Additionally the increased survival of SZC seen could be the result of natural adaptive immunity following previous exposure.…”
Section: Discussionmentioning
confidence: 88%
“…Cattle were defined as inbred using a method adapted from Murray et al (2013), which we described here. Non-ET introgressed cattle were categorised as inbred if they had an inbreeding coefficient value of greater than 0.184 (more than 0.10 above the mean for this group).…”
Section: Methodsmentioning
confidence: 99%